The Role of the Baker Division in Maintaining the Brand Image to Attract Consumer Interest in Buying at Dough Lab Plaza Senayan - Pradini, Gagih; Kusumaningrum, Anisa Putri; Jahmi, Muhammad Rijwan (Akademi Komunitas MAPINDO, 2024)
This research aims to examine the role of the Baker Division in maintaining brand image to increase consumer purchase interest at Dough Lab Plaza Senayan. The main focus of this study is to analyze the roles undertaken by the baker staff in baking products, using quality ingredients, and directly interacting with consumers. The research method used is qualitative with several informants consisting of area managers, baker staff, and consumers. The results of the study indicate that product innovation, the role of bakers in baking, and good interaction with consumers are key factors in attracting purchase interest. In addition, the success in increasing consumer purchase interest is also influenced by social media marketing strategies. Thus, this study concludes that the role of the baker division is crucial in building and maintaining a positive brand image, which ultimately can increase consumer purchase interest at Dough Lab Plaza Senayan.